Collection of Waste Electrical and Electronic Equipment at the European Level - Mihaela Hrisanta Mosora; Mirela Ionela Aceleanu; Lucian Alexa; Anca Maria Gherman; Cosmin Liviu Mosora (Amfiteatru Economic, 2023)
Currently, to ensure the sustainable development of any economy, a very important role is represented by the transition to the circular economy, which manifests itself differently by sectors and types of products. Considering the need to expand the circular economy, a special role is played by the production and consumption of electrical and electronic equipment. The objective of this article is to identify the factors that can influence the collection of electronic and electrical equipment at the European Union level. The methods used are statistical and econometric ones. Based on a panel regression, the study shows the specifics of the collection of electrical and household appliances, depending on several factors, such as the type and size of the appliances, the amount of electrical and electronic equipment (EEE) placed on the market, and the legislative measures taken at the European level. The main results highlight the degree of collection of electrical and electronic equipment according to its type and size; the highest degree of collection being recorded for household appliances. The originality of the paper consists in the identification of the characteristics of the collection of waste electrical and electronic equipment (WEEE), using the econometric method, the research being useful not only for the parties involved in the collection of waste electrical and electronic equipment (WEEE), but also for the decision makers, in order to improve the collection policies for this equipment.
Keywords: Q53; Q57; 330; Electronic and electrical waste equipment; collection; recycling; circular economy.